Zinc ion induced three-dimensional Co9S8 nano-neuron network for efficient hydrogen evolution. (September 2020) - Dong, Bin; Xie, Jing-Yi; Wang, Nan; Gao, Wen-Kun; Ma, Yu; Chen, Tian-Shu; Yan, Xin-Tong; Li, Qing-Zhong; Zhou, Yu-Lu; Chai, Yong-Ming
Abstract: As the cost-effective and nontoxic alternative for hydrogen evolution reaction (HER), Co9 S8 has attracted much attention. This paper explores the regulation of Zn doping impacted the unique nanostructure and electrocatalytic performance on Co9 S8 . Herein, utilizing copper foam (CF) as substrate, a series of different nanostructure of (Zn-)Co9 S8 @CF has been synthesized by accurately varying the ratio of Zn 2+ to Co 2+ . Compared with aggregated pure Co9 S8 and other different ratios contrast samples, Zn–Co9 S8 @CF-(1-1) with a zinc to cobalt ratio of 1 possesses highly dispersity which can be attributed to the novel nano-neuron network structure. The electrochemical measurements for HER demonstrate that Zn–Co9 S8 @CF-(1-1) not only reveals superior activity with small overpotentials to achieve a current density of 10 mA cm −2 in acidic (278 mV) and alkaline (273 mV) media, but also exhibits long-time durability in the solution with a wide range of pH. The excellent performance of Zn–Co9 S8 @CF-(1-1) can be attributed to the unique reticular structure which can facilitate exposure of numerous active sites and favorable long-term stability. The substrate of three-dimensional CF can provide the remarkable conductivity. This work provides a precise and effective approach to regulate three-dimensional nanostructure of Zn-doped electrocatalysts for HER. Graphical abstract: Image 1 Highlights: Zn–Co9 S8 on copper foam (CF) with a nano-neuron network structure is synthesized. The ratios of Zn 2+ to Co 2+ can affect the structure of Zn–Co9 S8 @CF. Zn–Co9 S8 @CF exhibits excellent activity and long-time durability with a wide range of pH. Zn doping is a promising method for construct the novel structure of electrocatalysts.